Solitary intraosseous neurofibroma of mandible. - Vivek N (Indian Journal of Dental Research, 2006)
Solitary intraosseous neurofibroma is a rare benign non-odontogenic tumor. Although neurofibromas occur predominantly as a feature of neurofibromatosis affecting the soft tissue, a few cases of solitary intraosseous neurofibromas of the jaw have been reported. We herewith report a case of solitary intraosseous neurofibroma of mandible in a middle-aged woman with a discussion on its clinical, radiological, and histopathological presentation along with review of cases.